Lipid A Has Significance for Optimal Growth of Coxiella burnetii in Macrophage-Like THP-1 Cells and to a Lesser Extent in Axenic Media and Non-phagocytic Cells - Wang, Tao; Yu, Yonghui; Liang, Xiaofei; Luo, Shengdong; He, Zemin; Sun, Zhihui; Jiang, Yongqiang; Omsland, Anders; Zhou, Pei; Song, Lihua (Frontiers in Cellular and Infection Microbiology, 2018)
Lipid A is an essential basal component of lipopolysaccharide of most Gram-negative bacteria. Inhibitors targeting LpxC, a conserved enzyme in lipid A biosynthesis, are antibiotic candidates against Gram-negative pathogens. Here we report the characterization of the role of lipid A in Coxiella burnetii growth in axenic media, monkey kidney cells (BGMK and Vero) and macrophage-like THP-1 cells by using a potent LpxC inhibitor -LPC-011. We first determined the susceptibility of C. burnetii LpxC to LPC-011 in a surrogate E. coli model. In E. coli, the minimum inhibitory concentration (MIC) of LPC-011 against C. burnetii LpxC is less than 0.05 μg/mL, a value lower than the inhibitor’s MIC against E. coli LpxC. Considering the inhibitor’s problematic pharmacokinetic properties in vivo and Coxiella’s culturing time up to seven days, the stability of LPC-011 in cell cultures was assessed. We found that regularly changing inhibitor-containing media was required for sustained inhibition of C. burnetii LpxC in cells. Under inhibitor treatment, Coxiella has reduced growth yields in axenic media and during replication in non-phagocytic cells, and has a reduced number of productive vacuoles in such cells. Inhibiting lipid A biosynthesis in C. burnetii by the inhibitor was shown in a phase II strain transformed with chlamydial kdtA. This exogenous KdtA enzyme modifies Coxiella lipid A with an α-Kdo-(2→8)-α-Kdo epitope that can be detected by anti-chlamydia genus antibodies. In inhibitor-treated THP-1 cells, Coxiella shows severe growth defects characterized by poor vacuole formation and low growth yields. Coxiella progenies prepared from inhibitor-treated cells retain the capability of normally infecting all tested cells in the absence of the inhibitor, which suggests a dispensable role of lipid A for infection and early vacuole development. In conclusion, our data suggest that lipid A has significance for optimal development of Coxiella-containing vacuoles, and for robust multiplication of C. burnetii in macrophage-like THP-1 cells. Unlike many bacteria, C. burnetii replication in axenic media and non-phagocytic cells was less dependent on normal lipid A biosynthesis.